Common pediatric medical procedures. Heart murmurs - Baum, Rebecca; American Academy of Pediatrics ([Elk Grove Village, Illinois] : American Academy of Pediatrics, 2018)
A complete review and demonstration of the examination for heart murmurs, including an overview of murmur grades and positioning techniques.
Presenter: Rebecca Baum.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed October 15, 2020)
Keywords: Heart murmurs in children -- Diagnosis; Heart -- Examination; Pediatrics; Documentary films; Instructional films; Nonfiction films; Internet videos; Streaming video; Short films